2012
DOI: 10.1103/physrevb.85.174409
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization and magnetization reversal in epitaxial Fe/Cr/Co asymmetric spin-valve systems

Abstract: We have investigated asymmetric Fe/Cr/Co/Cr superlattices with two magnetic layers of Fe and Co, which are different with respect to their magnetic properties: magnetization, coercivity, and magnetic anisotropy. The magnetic layers are weakly coupled via a mediating Cr spacer layer providing an antiferromagnetic alignment of adjacent layers. The magnetic structure of these spin-valve-like Fe/Cr/Co/Cr superlattices was analyzed from the remanent state up to saturation via polarized neutron scattering and polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This study was also significantly motivated by the surface induced unusual magnetic properties of spin reorientation transition on Cu (100) [5] and order-disorder magnetization on C (100) [6] with the Fe concentration of epitaxial grown ultra thin Fe x Co 100-x alloy. In particular, it has been reported that molecular beam epitaxially (MBE) grown ultra thin film of Fe and Co forms a superlattice structure on the Cr interface layer [7,8]. This report focuses on illustrating a nonmonotonic increase in the H c and relative magnetic moment with Fe concentration on Fe x Co 100-x /Cr (100).…”
Section: Introductionmentioning
confidence: 97%
“…This study was also significantly motivated by the surface induced unusual magnetic properties of spin reorientation transition on Cu (100) [5] and order-disorder magnetization on C (100) [6] with the Fe concentration of epitaxial grown ultra thin Fe x Co 100-x alloy. In particular, it has been reported that molecular beam epitaxially (MBE) grown ultra thin film of Fe and Co forms a superlattice structure on the Cr interface layer [7,8]. This report focuses on illustrating a nonmonotonic increase in the H c and relative magnetic moment with Fe concentration on Fe x Co 100-x /Cr (100).…”
Section: Introductionmentioning
confidence: 97%
“…4 In Ref. 5, it was shown that the non-collinearity of the layer magnetization may even be induced by stray fields from already deposited ferromagnetic domains acting on the magnetic alignment of the spins of atoms arriving at the surface of a growing film. Even more complex are asymmetric superlattices of the type [F 1 /N/F 2 /N] Â n with different ferromagnetic layers F 1 and F 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This was recently demonstrated for laterally extended [Fe/Cr/Co/Cr] superlattices using Polarized Neutron (specular) Reflectivity (PNR) and Polarized Neutron (off-specular) Scattering (PNS) methods. 5 In this contribution, we aim to study the magnetic properties of asymmetric [Fe/Cr/Co/Cr] superlattices which are laterally patterned into an array of parallel stripes. Patterning first of all introduces a uniaxial shape anisotropy, the strength of which depends on the aspect ratio of the stripes (length versus width).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most complete information is then gained if the neutron polarization of the scattered neutrons is analyzed for various spin states of the incident beam with respect to specular reflectivity and offspecular scattering. Polarized neutron reflectivity (PNR) is mainly used for the investigation of magnetic thin films, 14 superconducting thin films, 15,16 magnetic domains in continuous superlattices, [17][18][19][20][21] or laterally micro-and nano-patterned multilayers. [22][23][24][25][26][27] A detailed account on polarized neutron reflectometry is available in recent reviews.…”
Section: Introductionmentioning
confidence: 99%